The effect of management team characteristics on performance and style extremity of mutual fund portfolios - Liu Qiong; Kuan Yang; Yinggao Zhou (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Along with mutual funds' scale and quantity expanding for our country, it is common for fund management companies hiring new managers or the original fund managers mobilizing from one to another. The high liquidity of fund managers makes different managers regroup to manage the funds that belong to the same fund management company in each fund year. The characteristics of these different management team will influence the fund performance, and also affect the earnings of the fund management company and portfolio investors. The purpose of this paper is as follows. First, evaluating the effect of management team characteristics on portfolio characteristics: risk, performance, and extremity. Second, testing the hypothesis that the ranking of mid-year performance have effect on investment style extremity and research what relationship exists between this phenomenon and management team characteristics in depth. Design/methodology/approach: On the analysis of the relationships between the management team characteristics and portfolio characteristics, a series of OLS regressions is run where the time series regression model (the factor model) and cross-sectional regression are included based on using the STATA, EVIEWS and MATLAB. The validity and practicability of the model will be verified in the paper. All of the above are aimed at achieving portfolio optimization and realizing the maximization of the interests of fund management companies and investors. Findings: The main findings are as follows. Teams with more doctors or MBA (CPA and CFA) hold more risky portfolios, while teams with long team tenure hold less. More members and large gender diversity have negative effect on performance, and the opposite is age diversity. Teams with more members and long tenure tend to hold less extreme style decisions, but age diversity is related to more. Besides, tournament hypothesis does exist in China investment funds industry especially when the economy is in a downward phase, and fund managers are more likely to raise the risk of portfolio when their term is coming to an end. Practical implications: These findings have important implications for fund management companies as they try to form a highly efficient management team as well as for individual investors' investment allocation decisions. Originality/value: This paper propose a new perspective to evaluate the relationship between the management team characteristics and portfolio characteristics, which focus on both sides investors rather than a single fund.
Keywords: 650; financial engineering; mutual fund portfolios; management team characteristics; style extremity; tournament hypothesis